Rethinking Financial Deepening : Stability and Growth in Emerging Markets - Sahay, Ratna; Barajas, Adolfo; Cihak, Martin; N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2015)
The global financial crisis experience shone a spotlight on the dangers of financial systems that have grown too big too fast. This note reexamines financial deepening, focusing on what emerging markets can learn from the advanced economy experience. It finds that gains for growth and stability from financial deepening remain large for most emerging markets, but there are limits on size and speed. When financial deepening outpaces the strength of the supervisory framework, it leads to excessive risk taking and instability. Encouragingly, the set of regulatory reforms that promote financial depth is essentially the same as those that contribute to greater stability. Better regulation-not necessarily more regulation-thus leads to greater possibilities both for development and stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet